Program dan Peran Keluarga dalam Mendukung Children’s Wellbeing - Ghaida Al Magfira; Risbon Sianturi; Izmi Balkis R; Setiawati Dewi Pratiwi; Suci Malkah Nur Azizah (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
Children’s wellbeing is a multidimensional concept that includes physical, psychological, social, and cognitive aspects of child development. The family plays a central role as the primary environment influencing children’s growth and overall welfare. However, modern challenges such as limited parenting knowledge, economic pressures, and digital distractions often reduce the quality of family interaction and parenting practices. This study aims to examine the concept of children’s wellbeing, analyze the role of family in supporting it, identify effective family programs and policies, and provide recommendations for optimizing family involvement. This research uses a literature review approach by analyzing various scientific sources related to family roles, parenting practices, and child wellbeing. The findings indicate that positive parenting, emotional support, parental involvement, and structured family programs such as parenting education, health programs, early stimulation, and social protection policies significantly contribute to children’s wellbeing. Collaboration between families, communities, educational institutions, and government policies is essential to create a supportive environment for children. Strengthening family-based programs and improving parenting literacy are key strategies to ensure children grow in a safe, supportive, and developmentally appropriate environment